Effect Of Pipe Roof Support On The Ground Settlement Induced By Shallow Tunnel Excavation - Abdul Latif, Mohd Fandey (2016)
Nowadays, underground space has become an important part of human development involving economics, social and needs. Some areas especially in the urbanized surroundings are in need of a better solution for an efficient transportation system. Shallow tunnel usually constructed beneath an existing highway or an area with limited spaces to improve transportation network. In the present study, pipe roof support was analyzed to determine the optimum function of its system that acts as a temporary support. The pipe roof is formed by installing a number of horizontal concrete piles at the crown of the tunnel by using microtunnelling boring machine (MTBM). The analyses were done in a few separate cases by using 2D-Finite Element modeling. The models were differentiated according to three tunnel shapes which are circular, horseshoe and square. Each tunnel had been analyzed according to the effect of the pipe roof tunnel to depth (0.0d, 0.5d, 1.0d and 2.0d) and spacing between twin tunnels (0.0d, 0.5d, 1.0d and 2.0d). The last part of the analyses is the verification study on a pipe roof tunnel project at Padang Rengas, Perak. A simple ground profile of the tunnel project had been created by using the information gathered from the bore log of the in-situ. Based on the analyses, the results had shown that the settlement has been reduced up to 90% with the installation of pipe roof system. As the tunnel depth increase, the magnitude of settlement above the tunnel has reduced up to 60%. Meanwhile, for the twin tunnels, the magnitude of settlement has increased up to 70% at the second tunnel due to the excavation of the first tunnel that cause disturbance to the soil strength. The magnitude of settlement of a twin tunnels also reduced from up to 58% when the spacing between the tunnels increase.